TRPA1 mediates amplified sympathetic responsiveness to activation of metabolically sensitive muscle afferents in rats with femoral artery occlusion - Xing, Jihong; Lu, Jian; Li, Jianhua (Frontiers in Physiology, 2015)
Autonomic responses to stimulation of mechanically and metabolically sensitive muscle afferent nerves during static contraction are augmented in rats with femoral artery occlusion. Moreover, metabolically sensitive transient receptor potential cation channel subfamily A, member 1 (TRPA1) has been reported to contribute to sympathetic nerve activity (SNA) and arterial blood pressure (BP) responses evoked by static muscle contraction. Thus, in the present study, we examined the mechanisms by which afferent nerves’ TRPA1plays a role in regulating amplified sympathetic responsiveness due to a restriction of blood flow directed to the hindlimb muscles. Our data show that 24-72 hrs of femoral artery occlusion 1) upregulates the protein levels of TRPA1 in dorsal root ganglion (DRG) tissues; 2) selectively increases expression of TRPA1 in DRG neurons supplying metabolically sensitive afferent nerves of C-fiber (group IV); and 3) enhances renal SNA and BP responses to AITC (a TRPA1 agonist) injected into the arterial blood supply of the hindlimb muscles. In addition, our data demonstrate that blocking TRPA1 attenuates SNA and BP responses during muscle contraction to a greater degree in ligated rats than those responses in control rats. In contrast, blocking TRPA1 fails to attenuate SNA and BP responses during passive tendon stretch in both groups. Overall, results of this study indicate that alternations in muscle afferent nerves’TRPA1 likely contribute to enhanced sympathetically mediated autonomic responses via the metabolic component of the muscle reflex under circumstances of chronic muscle ischemia.